Acknowledging knowledge: The perception of knowledge requirements for public procurement officials and their professional development. Issue 1 (5th March 2018) - Williams, Adam M.; Lau, Fion; McCue, Clifford P.
Abstract : Purpose: The purpose of this paper is to examine the knowledge public procurement professionals perceive as important for performing their duties. Design/methodology/approach: Using secondary data generated from a job analysis study commissioned by the Universal Public Procurement Certification Council [UPPCC], this paper examined the knowledge sets that procurement officials recognize as necessary and sufficient for daily operations and professional development. Findings: Principal Component Analysis is used to validate the six domains of knowledge covered on the survey. This paper identifies sets of core knowledge domains that are essential for procurement administration, including sourcing, negotiation process, contract administration, supply management and strategic procurement planning. Originality/value: Furthermore, the authors incorporated anecdotal commentary information from the same survey to determine what additional professional development and continuing education opportunities procurement officials are seeking to improve performance in their current and future work roles.